Implementation Of Digital Media Promotion Strategies At Warung Parahyangan - Yuswardi Yuswardi; Chrisjunianti Chrisjunianti (Universitas Internasional Batam, 2023)
Warung Parahyangan is a business engaged in the culinary field, where the food served is mostly Sundanese specialties. Since the pandemic, the income earned by Warung Parahyangan has decreased because the business of Warung Parahyangan is run without the help of social media or other applications, only depending on consumers who come to the shop. However, at the beginning of 2022, when schools have started to conduct learning offline, it will provide a slight increase in income, because the main target of the shop is school students whose school is located right in front of the shop. However, most of the school students have lost interest in eating at Warung Parahyangan, apart from being afraid of going out of school considering the pandemic is not over yet, also because many new students don't know about Warung Parahyangan. based on existing problems, we help implement promotional strategies with the help of social media. The promotion strategy that we use is the creation of digital posters, Instagram accounts and also go-food accounts so that they can help build image and consumer loyalty to Warung Parahyangan.